SAT0513 ASSOCIATION OF SERUM OMENTIN LEVELS WITH COLCHICINE RESISTANCE IN FAMILIAL MEDITERRANEAN FEVER. (2nd June 2020) - Can Sandikci, S.; Omma, A.; Yucel, C.; Omma, T.
Abstract : Background: Omentin is an anti-inflammatory adipokine, which plays important roles in the adjustments of glucose metabolism, cardiovascular homeostasis, atherosclerosis (1). Objectives: To investigate the omentin levels in Familial Mediterranean fever (FMF) patients and to assess the association with markers of subclinical inflammation in FMF patients such as serum amyloid A (SAA), erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP). Methods: This cross-sectional study included 54 consecutive adult FMF patients (27 male, 27 female) and 28 healthy individuals (16 male, 12 female). The demographic and clinical features and MEFV gene mutations were recorded. The FMF patients were separated into 3 groups: 1) attack-free group, 2) active attack group and 3) colchicine-resistant group. Serum omentin levels were compared between the FMF patients and the healthy control group. Results: Serum omentin and SAA levels were higher in the study group than in the control group (108.05(19.97-343.22) vs. 199.5(42.98-339.41) p<0.05, 3.69(1.18-22.75) vs. 1.31(0.95-3.16) p<0.001) (Table 1 ). When the FMF patients were examined as separate groups, serum omentin values were lower in the colchicine resistant group than in the groups without resistance (Table 2 ). The correlation analysis showed a negative correlation between omentin and SAA levels (r = -0.240, p = 0.030). Conclusion: FMF patients with colchicine resistance are associated with decreased omentin concentrations, probably mediated by inflammation-driven mechanisms. References: [1]Yue J, Chen J, Wu Q, Liu X, Li M, Li Z, Gao Y. Serum levels of omentin-1 association with early diagnosis, lesion volume and severity of acute ischemic stroke. Cytokine. 2018;111:518–522. Disclosure of Interests: None declared